Existence and Uniqueness of Solution of Some Boundary Value Problems for Delay Differential Equations - E. ELjaneid, Nedal Hassan (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2017)
We presented as study to establish the existence and uniqueness of solution some three point boundary value problems for second order differential equations.